2014
DOI: 10.1175/jcli-d-14-00005.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Warm-Season Diurnal Variability over East Asia in Recent Reanalyses JRA-55, ERA-Interim, NCEP CFSR, and NASA MERRA

Abstract: Four recent reanalyses—the 55-yr Japanese Reanalysis Project (JRA-55), Interim ECWMF Re-Analysis (ERA-I), NCEP Climate Forecast System Reanalysis (CFSR), and NASA Modern-Era Retrospective Analysis for Research and Applications (MERRA)—are assessed to clarify their quality in representing the diurnal cycle over East Asia. They are found to present similar patterns/structure and summer progress of the mean wind diurnal cycle, whereas they exhibit some differences in diurnal amplitude, particularly for the low-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 40 publications
6
111
0
1
Order By: Relevance
“…The assimilation scheme of the four-dimensional variational method was adopted in JRA55 using the forecast model T319/L60 (a spatial resolution of approximately 60 km). Satellite data including ocean surface wind microwave scatterometers and radiances from vertical sounders and micro-wave imagers were assimilated such that the quality of JRA55 was improved compared with the existing reanalysis datasets (e.g., Chen et al 2014). The qualitative patterns of averaged large-scale fields with the JRA55 in this study are largely consistent with other objective analysis datasets (e.g., ERA-Interim, Dee et al 2011).…”
Section: Datasupporting
confidence: 72%
“…The assimilation scheme of the four-dimensional variational method was adopted in JRA55 using the forecast model T319/L60 (a spatial resolution of approximately 60 km). Satellite data including ocean surface wind microwave scatterometers and radiances from vertical sounders and micro-wave imagers were assimilated such that the quality of JRA55 was improved compared with the existing reanalysis datasets (e.g., Chen et al 2014). The qualitative patterns of averaged large-scale fields with the JRA55 in this study are largely consistent with other objective analysis datasets (e.g., ERA-Interim, Dee et al 2011).…”
Section: Datasupporting
confidence: 72%
“…Their evaluations revealed the improvement of JRA-55 in various aspects. For example, they evaluated the signatures of naturally induced variability in the atmosphere (Mitchell et al 2015), representation of the diurnal migrating tide in the stratosphere, extra-tropical cyclone activity, distribution of precipitation in the tropics, and diurnal cycle over East Asia (Chen et al 2014). Some of these evaluation studies are included in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Rahim et al (2013) showed a significant correlation between CFSR and QuikSCAT over the South China Sea. Most recently, Chen et al (2014) assessed the diurnal cycle of wind fields from the Japanese 55-year Reanalysis Project (JRA-55), ERA-Interim, CFSR, and the Modern-Era Retrospective Analysis for Research and Applications (MERRA) over East Asia using rawinsonde observation data from 22 sites over southern China. They noted that the four reanalysis datasets can represent the mean wind diurnal cycle, but they differ in the amplitude of the diurnal cycle.…”
Section: Datasets and Methodsmentioning
confidence: 99%